Integrity Test for Hepa Filters in Cleanroom Preparation and Cleanroom Process of Labled Compound - I Wayan Widiana; Hermanto Hermanto (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
One of some factors that take effect for the cleanroom sterilization is the integrity of HEPA filters. The value of HEPA filters integrity should be contained in the qualification document of air conditioning system (HVAC). HEPA filters integrity testing aims to ensure the performance of HEPA filters that installed in the air conditioning system, so that no leakage occurs in the installation of HEPA filters, that cause the cleanroom becomes unsterile. The methodology used is to supply aerosol concentration in the upper HEPA filter between 10 - 100 μg/L, and then perform a maximum aerosol penetration measurement on the downstream of HEPA filter. The results are compared with the standard provisions that is contained in the